AN ANALYSIS OF TEACHERS’ PERSONALITY COMPETENCE IN TEACHING ENGLISH AT SMK NEGERI 1 BOTOMUZOI IN 2024/2025 - LASE, RIANG; LAOLI, ADIELI; DAELI, HIDAYATI; TELAUMBANUA, KRISTOF MARTIN EFORI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Teacher personality competence plays a critical role in shaping the effectiveness of the learning process. It refers to the personal qualities and characteristics that a teacher brings to the classroom, influencing how they interact with students, manage the learning environment, and serve as role models. This competence includes indicators such as honesty, exemplary conduct, a strong work ethic, high responsibility, pride in the profession, and self-confidence. Research suggests that personality competence not only affects the teacher-student relationship but also contributes to students' academic and personal development. Through observation, interviews, and documentation, this study investigates the personality competence of English teachers at SMK Negeri 1 Botomuzoi. The findings reveal that while the teachers demonstrate several positive traits, there are areas where improvements are needed, particularly in self-discipline, responsibility, and demonstrating pride in the teaching profession. The study underscores the need for continuous professional development to enhance teachers' personality competence, which in turn can positively impact the overall educational experience for students. ABSTRAKKompetensi kepribadian guru memegang peranan penting dalam membentuk efektivitas proses pembelajaran. Kompetensi ini mengacu pada kualitas dan karakteristik pribadi yang dibawa guru ke kelas, yang memengaruhi cara mereka berinteraksi dengan siswa, mengelola lingkungan belajar, dan menjadi panutan. Kompetensi ini mencakup indikator seperti kejujuran, perilaku teladan, etos kerja yang kuat, tanggung jawab yang tinggi, kebanggaan terhadap profesi, dan kepercayaan diri. Penelitian menunjukkan bahwa kompetensi kepribadian tidak hanya memengaruhi hubungan guru-siswa tetapi juga berkontribusi terhadap pengembangan akademik dan pribadi siswa. Melalui observasi, wawancara, dan dokumentasi, penelitian ini menyelidiki kompetensi kepribadian guru bahasa Inggris di SMK Negeri 1 Botomuzoi. Temuan penelitian mengungkapkan bahwa meskipun guru menunjukkan beberapa sifat positif, ada beberapa hal yang perlu ditingkatkan, khususnya dalam hal disiplin diri, tanggung jawab, dan menunjukkan kebanggaan terhadap profesi guru. Penelitian ini menggarisbawahi perlunya pengembangan profesional berkelanjutan untuk meningkatkan kompetensi kepribadian guru, yang pada gilirannya dapat berdampak positif pada keseluruhan pengalaman pendidikan bagi siswa.